2004
DOI: 10.1091/mbc.e03-07-0497
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosed Cation-Independent Mannose 6-Phosphate Receptor Traffics via the Endocytic Recycling Compartment en Route to thetrans-Golgi Network and a Subpopulation of Late Endosomes

Abstract: Although the distribution of the cation-independent mannose 6-phosphate receptor (CI-MPR) has been well studied, its intracellular itinerary and trafficking kinetics remain uncertain. In this report, we describe the endocytic trafficking and steady-state localization of a chimeric form of the CI-MPR containing the ecto-domain of the bovine CI-MPR and the murine transmembrane and cytoplasmic domains expressed in a CHO cell line. Detailed confocal microscopy analysis revealed that internalized chimeric CI-MPR ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 61 publications
7
112
0
1
Order By: Relevance
“…Briefly, CD8 WT (CD8-WT) contains no known sorting signals in its cytoplasmic tail, is therefore not subject to endocytosis and is resident at the plasma membrane (28). CD8-cation-independent mannose 6-phosphate receptor (CIMPR) contains the cytoplasmic domain of CIMPR, a wellcharacterized cargo that is efficiently internalized in clathrincoated vesicles before being trafficked to the trans-Golgi network (TGN) and a subset of late endosomes, via sorting and recycling endosomes (32,33). The remaining constructs contain "designer" tails that represent three well-established endocytic motifs: YXXΦ (CD8-YAAL), [DE]XXXL[LI] (CD8-EAAALL), and FXNPXY (CD8-FANPAY), all transposed on a background of eight alanines (CD8-8xA) (28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, CD8 WT (CD8-WT) contains no known sorting signals in its cytoplasmic tail, is therefore not subject to endocytosis and is resident at the plasma membrane (28). CD8-cation-independent mannose 6-phosphate receptor (CIMPR) contains the cytoplasmic domain of CIMPR, a wellcharacterized cargo that is efficiently internalized in clathrincoated vesicles before being trafficked to the trans-Golgi network (TGN) and a subset of late endosomes, via sorting and recycling endosomes (32,33). The remaining constructs contain "designer" tails that represent three well-established endocytic motifs: YXXΦ (CD8-YAAL), [DE]XXXL[LI] (CD8-EAAALL), and FXNPXY (CD8-FANPAY), all transposed on a background of eight alanines (CD8-8xA) (28).…”
Section: Resultsmentioning
confidence: 99%
“…This pool is likely due to different trafficking routes. Although proteins containing YXXΦ, [D/E]XXXL[L/I], or FXNPXY motifs typically show rapid recycling back to the plasma membrane after internalization, a proportion of CIMPR also traffics to the TGN and late endosomes (33). Recycling from here to the plasma membrane will necessarily take more time.…”
Section: Mitotic Inhibition Of Endocytosis Was Confirmed Using Fluorementioning
confidence: 99%
“…For instance, in mammalian cell pulse-chase experiments, TGN38 and Shiga toxin have been shown to be retrograde cargos that traverse the recycling endosome en route to the TGN (20,21,25). Canonical recycling endosome regulators Rab11, FIP1/RCP, and mRme-1/EHD1 have been shown to be important regulators of recycling endosome-to-TGN transport of retrograde cargo (23,25,54). However, the overall molecular mechanisms mediating this transport step have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has revealed that M6PR moves between the Golgi and endosomes along diverse recycling pathways (Ghosh et al, 2003;Bonifacino and Rojas, 2006). Recycling endosomes and late endosomes are among the endocytic compartments from which M6PR returns back to the Golgi complex (Klumperman et al, 1993;Hirst et al, 1998;Lin et al, 2004;Tortorella et al, 2007). Consequently, we analyzed the subcellular distribution of the mannose-6-phosphate receptor (M6PR) in control and hSPE-39 downregulated cells.…”
Section: Hspe-39 Is Required For M6pr-mediated Transportmentioning
confidence: 99%